Information technology in Philippine libraries an analysis using the Hegelian Dialectic - Ileto, Dina I.; Obille, Kathleen Lourdes B.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2016)
This research determined the evolution of the library and its dichotomy with technology and identified progress of change in the library, librarianship and library services in the country. By attaining the objectives of this study, the current state of the libraries in the Philippines was determined and by applying the dialectics of Hegel (thesis, antithesis and synthesis), the Philippine libraries' different turning points were identified. Finally, the research examined these turning points and their importance to the study of Information and Library Science. This study referred to and reviewed qualitative research from electronic databases and published works.
Researches relevant to the topic of technological adoption, and their application to organization' Information Technology (IT) adoption, both directly or indirectly related to the topic, were considered for this study. The main part of the research was sourced from recent lecture presentations, journal topics and Powerpoint presentations. It application to the Philippine libraries' recent studies was mainly about the infusion of technology in different formats and in different degrees of requirements of each library.
All relevant articles and published works gathered were thoroughly read, reviewed and evaluated. All possible relevant topics were used to achieve the objectives of this study. The stream of events, as well as other factors--such as war, creation and implementation of laws and other environmental changes--played a major role in the shift in focus of library development. Using Hegel's dialectics of thesis, antithesis and synthesis, the study was able to delineate the dynamic changes of the library. From an institution focused on educating the Filipino people, the library has blossomed into an institution that develops the ability of Filipinos to transform their own technology-based instruments and their own tools for providing service.
Librarianship likewise developed into a profession which led to the enactment of library laws primarily aimed at developing library study in the country. The study recommended the further development of links between library sectors and organizational resources for a better access to written documentation of these advancements for all library sectors in the country.
A collective effort must be launched by concern sectors to create a massive awareness regarding the situation of libraries in the country. The Philippine National Library, as the country's mandated repository of information in the country, should develop one cohesive and collective historical identity of libraries in the country. This will help support and navigate the future mapping of the evolution of libraries and librarianship in the country.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Philippines